Explorando outros cenários: o serviço social no espaço escolar - Oliveira, Jullymara Lais Rolim de (2013)
Education as a public policy is a contradictory space of class struggles, tensioned social projects in contention, which has historically characterized by a ballast of ideological battles, economic and social. In this sense, the school is one of the spaces in which they reveal the contradictions of the capitalist system and where manifest numerous expressions of social issues. In recent years, public education, private and philanthropic Brazil, has been configured as an emerging area of activity of the social worker and meets the needs of increasing socio- institutional conditions of access, retention and democratization processes and the quality of education in different levels and types of education. For this bias , this dissertation is aimed to analyze the Social Service in the school, highlighting the theoretical- methodological, ethical-political and technical- operative present in the professional practice of social workers in the schools of João Pessoa. The study was part of the assumptions of an analysis of quantitative and qualitative research, based on the principles of content analysis with an exploratory approach and the light of dialectical critical method. It was found that the performance of social work is presented through activities involving planning, implementation and monitoring, seeking student development and citizenship through access and stay in school. The insertion of the social worker in education does not constitute a recent phenomenon, but remote to the early years of the profession, this insertion has regional and local peculiarities, in this perspective, the survey provided an opportunity us to identify the deployment process, legitimation and maturation of practice professional in the school of municipal schools in João Pessoa -PB. The survey results indicate that the professional practice of social worker is part of a field riddled with limitations and challenges, but also many possibilities. The social worker in the school operates from the perspective of defense and guarantee of rights, especially in mediating between family / school / community / social protection network, through a multidisciplinary and interdisciplinary work. Without pretending to exhaust the subject, the study provides a reading of these issues with the scope to provide a contribution on this theme.